Low-Density Lipoprotein Receptor Gene Mutation Analysis and Structure–Function Correlation in an Omani Arab Family With Familial Hypercholesterolemia. (November 2014) - Al-Rasadi, Khalid; Al-Waili, Khalid; Al-Zidi, Ward Al-Muna; Al-Abri, Abdul Rahim; Al-Hinai, Ali T.; Al-Sabti, Hilal Ali; Al-Tobi, Sheikha; Al-Zakwani, Ibrahim; Al-Zadjali, Fahad; Al-Hashmi, Khamis; Banerjee, Yajnavalka
Familial hypercholesterolemia (FH) is an autosomal dominant disorder typified by elevated low-density lipoprotein cholesterol (LDL-C) levels caused by mutations in the LDL receptor (LDLR), apolipoprotein B (ApoB), or proprotein convertase subtilisin/kexin type 9 ( PCSK9 ) genes. Previously, we reported a novel mutation in the exon-3 of LDLR gene, observed in a 9-year-old Omani Arab female. Here, we investigated the mode of inheritance of this mutation and confirmed that FH in this family is due to mutation only in the LDLR and not PCSK9 and ApoB genes. Further, the effect of the mutation has been appraised in silico on the tertiary structure of LDLR. A model of the mutant LDLR has been constructed using the coordinates of the wild-type LDLR extracellular domain. Based on the model, we present a mechanistic justification behind the observed detrimental effect of the mutation on LDL-C levels.